Correction: Corrigendum: Small genomic insertions form enhancers that misregulate oncogenes - Brian J. Abraham (Nature Portfolio, 2017)
Nature Communications 8: Article number:14385 (2017); Published: 9 February 2017; Updated: 1 June 2017 In the original version of Supplementary Data 1 associated with this Article, the list of predicted enhancer-associated insertions was inadvertently truncated. The HTML has now been updated to include the correct version of the Supplementary Data 1.